2008
DOI: 10.2214/ajr.07.2699
|View full text |Cite
|
Sign up to set email alerts
|

MDCT and Radiography of Wrist Fractures: Radiographic Sensitivity and Fracture Patterns

Abstract: Thirty percent of wrist fractures were not prospectively diagnosed on radiography, suggesting that CT should be considered after a negative radiographic finding if clinically warranted. The location of a dorsal scaphoid avulsion fracture emphasizes the need for specific radiographic views or cross-sectional imaging for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
2
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 22 publications
8
69
2
8
Order By: Relevance
“…Therefore, it can be assumed that early diagnosis and treatment planning cannot be assured if diagnosis relies on biplane radiography only. This is in concordance with recent reports supporting MDCT as a diagnostic modality of high diagnostic accuracy in scaphoid fracture detection [23][24][25][26] whereas in these reports radiography also was of limited value [23,25,27] . Stevenson et al [24] showed that using initial MDCT an occult scaphoid fracture can be ruled out with the patient returning to regular activity immediately.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, it can be assumed that early diagnosis and treatment planning cannot be assured if diagnosis relies on biplane radiography only. This is in concordance with recent reports supporting MDCT as a diagnostic modality of high diagnostic accuracy in scaphoid fracture detection [23][24][25][26] whereas in these reports radiography also was of limited value [23,25,27] . Stevenson et al [24] showed that using initial MDCT an occult scaphoid fracture can be ruled out with the patient returning to regular activity immediately.…”
Section: Resultssupporting
confidence: 92%
“…A previous report found that only 20% of triquetrum fractures were identified on plain radiographs [10]. Given the morbidity associated with non-union of triquetrum body fractures, we advocate a high index of suspicion for these fractures in people who have fallen on an outstretched hand, and present with ulnar-sided wrist pain.…”
Section: Discussionmentioning
confidence: 85%
“…Bununla beraber, büyük bir hasta sayısının oldugu bazı çalışmalar göstermiştir ki, konvansiyonel radyografi karpal kırıkların tespitinde yetersiz kalmaktadır (8,9) . Tomografinin el bileğindeki kırıkların tespitinde tatmin edici duyarlılığa sahip oldugu da çalışmalarda belirtilmiştir (10) .…”
Section: Discussionunclassified